Evaluasi Pengelolaan Ekstrakurikuler Sepak Bola Untuk Meningkatkan Prestasi Non Akademik Di SMA Negeri 3 Kota Bengkulu - Saputra, Decky; Nur Sasongko, Rambat; Connie (UNIVERSITAS BENGKULU, 2024)
Extracurricular activities are activities held outside school hours. Extracurriculars are also a means to develop students' talents and interests in non-academic fields, especially in the field of football and to achieve achievements in the field of football. Good football extracurricular management can support the achievement of football extracurricular goals. The aim of this research is to evaluate the management of the football extracurricular program at SMA Negeri 3 Bengkulu City. This evaluation consists of: 1. Context evaluation includes: (a) the nature of extracurricular activities for students, teachers and society; 2. Input evaluation includes; (a) competence of supervising teachers, (b) learning materials, (c) extracurricular support; 3. Process evaluation includes; (a) student activity and condition, (b) extracurricular activity organizers, (c) evaluation of extracurricular activities; 4. Product evaluation includes; (a) development of student behavior, (b) student achievement. This research is a type of program evaluation research using the CIPP model (context, inputs, process, product). This research was conducted at SMA Negeri 3 Bengkulu City.